The Polish model of a social economy with the financial aspects and profits at background: From the general theory to practice - Katarzyna J. Chojnacka (e-Finanse: Financial Internet Quarterly, 2019)
This article contains main trends, assumptions and thesis about the social economy in Poland, which the author agree with. The main goal of it, is to bring together fundamental facts depicting the situation of the social economy in Poland (in theory and in practice) with the conditions that must be fulfilled in order for it to grow (also from the financial side). In the article, the aspect of profit in a social enterprise, was especially emphasized. To describe the topic the descriptive methods were used. The graphical analysis refers to the last three years, but to understand how the social economy operates in practice, author uses description of the data from 1999 to now, in this paper.
Keywords: B55; G41; L31; L33; 330; social economy; social entities; profits; social enterprises